DIALEK DAN BACAAN DALAM AL-QURAN: MENGURAI PERBEDAAN ANTARA SAB'AH AHRUF DAN QIRA'AH SAB'AH - Khozainul Ulum (Al Hikmah: Jurnal Studi Keislaman, 2015)
As already known that the Arab nation is composed of several clans or tribes with one language, namely Arabic. Although their language is the same, each tribe has its own dialect (lahjah) that is different from each other. In fact, most of the tribes would likely be difficult to use the dialect of others.This difficulty also occurs in the utterances of the Koran which is both initially and partially revealed in the Quraishi Arabic. Therefore, in a hadiththe Prophet (PBUH) asked Gabriel to recite the Quran not just one but seventy harf, popularly known as sab'ah ahruf. In addition, there is another term that some people considered the same as sab'ah ahruf, namely qira'ah sab'ah. In this case, the raising question is that is the sab'ah ahruf the same as qira'ah sab'ah or are both different from each other.